Physical performance with EPTS analysis in national team soccer players vs. local Paraguayan competition - Segales, Dulce; Cofre-Bolados, Cristian; Farias Valenzuela, Claudio; Fabres, Ignacio; Barrows Formantel, Sebastián (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
In the senior team of Paraguay since mid-2020, profiles have been carried out by positions that allow us to understand a gold standard, and in this way quickly compare player profiles to relate them to the models found in the local league. The aim of this study was to determine the physical performance of the soccer players of the local league of Paraguay vs. the National Team, relating the analysis by position between Front Markers, Central Markers and Wingers. The sample consisted of 176 professional soccer players: 149 of the local tournament belonging to 6 first division clubs, measured with electronic performance and tracking systems (EPTS). The data for the national team corresponded to 27 players measured in the competition matches of the Qualifier for Qatar 2022 and Copa América 2021. The results indicated that there were no differences in maximum speed between the national team and players of the local tournament. In a distance traveled greater than 24 km/h, there was a difference in the extremes in favor of those selected. In a distance greater than 18 km/h, there was no difference. In acceleration distance there were no differences in the two groups analyzed. Finally, in total distance traveled, there was only a difference in central markers in favor of the local group.